The Anomaly of Leading Indicator - Lydia I. Kumajas; Novie Rarung; Natalia A. Malau (Journal of International Conference Proceedings (JICP), 2022)
The counter cyclical strategy used to deal with the Covid-19 pandemic is through fiscal policy, government expenditure by refocusing on the health sector and economic recovery. This policy is not only carried out in Indonesia but in other affected countries. In general, government expenditure has made positive impact on GDP, but during the COVID-19 pandemic this affect became negative. Using data from 137 countries, government health expenditure has a negative impact on GDP. If government expenditure policies continue to focus on health care, it will have an impact on other sectors, ultimately negative economic growth. In addition to refocusing on health expenditure, there are also assistance programs for affected communities. Higher aid should affect the GDP, but there is no difference in GDP growth between the two groups of countries based on the percentage of income support. Government expenditure policies in each country certainly aim to maintain the stability of the country, but the policy objectives should be allocated not only curatively but also preventively by taking into account the long-term impact post covid-19 Era. Keywords: GDP, Government Expenditure, Government Health Expenditure, Income Support, Refocusing.